PBB Digitalization: Analysis of the Effectiveness of E-PBB in PBB-P2 Data Collection in Langkat Regency - Mariono, Mariono; Junita, Audia; Jamaludin, Yanhar (Borong Newinera Publisher, 2025)
This study aims to analyze the effectiveness of the implementation of E-PBB in PBB-P2 data collection in Lalat Regency. The E-PBB system is expected to increase efficiency, accuracy, and transparency in the management of taxpayer data, as well as accelerate the process of data collection and tax payment. This study uses a qualitative approach with interview, observation, and documentation methods to explore information related to the implementation of E-PBB, supporting factors, and obstacles in the tax digitization process in Langkat Regency. The results of the study show that E-PBB has a positive impact in accelerating and simplifying the taxpayer data collection process. However, several obstacles, such as the low digital literacy of the community and the limitations of technological infrastructure, are still challenges in optimizing this system. Support from local governments and the use of digital payment platforms are the main supporting factors, while limited internet networks and lack of socialization are significant inhibiting factors. The study suggests increasing education and socialization to the public, improving technological infrastructure, and providing incentives to taxpayers who use digital systems to increase their participation in tax reporting and payment. Thus, it is hoped that the implementation of E-PBB can be more effective in supporting better data collection and regional tax revenue in the future.